The Effect of Individual Musculoskeletal Conditions on Depression: Updated Insights From an Irish Longitudinal Study on Aging - Jin, Wenyi; Liu, Zilin; Zhang, Yubiao; Che, Zhifei; Gao, Mingyong (Frontiers in Medicine, 2021)
Few longitudinal studies have systematically investigated whether or how individual musculoskeletal conditions (IMCs) convey risks for negative psychological health outcomes, and approaches to assess such risk in the older population are lacking. In this Irish nationally representative longitudinal prospective study of 6715 individuals aged 50 and over, machine learning algorithms and various models, including mediation models, were employed to elaborate the underlying mechanisms of IMCs leading to depression and to develop an IMC-induced negative psychological risk (IMCPR) classification approach. Resultantly, arthritis (odds ratio [95% confidence interval]: 2.233 [1.700-2.927]), osteoporosis (1.681 [1.133-2.421]), and musculoskeletal chronic pain (MCP, 2.404 [1.838 to 3.151]) were found to increase the risk of depression after two years, while fracture and joint replacement did not. Interestingly, mediation models further demonstrated that arthritis per se did not increase the risk of depression; such risk was augmented only when arthritis-induced restrictions of activities (ARA) existed (proportion of mediation: 316.3% [ARA of usual], 213.3% [ARA of social and leisure], and 251.3% [ARA of sleep]). The random forest algorithm attested that osteoarthritis, not rheumatoid arthritis, contributed the most to depressive symptoms. Moreover, bone mineral density was negatively associated with depressive symptoms. Systemic pain contributed the most to the increased risk of depression, followed by back, knee, hip, and foot pain (mean Gini-Index: 3.778, 2.442, 1.980, 1.438, and 0.879, respectively). Based on the aforementioned findings, the IMCPR classification approach was developed using an interpretable machine learning model, which stratifies participants into three grades. Among the IMCPR grades, patients with a grade of “severe” suffered higher odds of depression than those with “mild” (odds ratio [95% confidence interval]: 4.055 [2.907-5.498]) or “moderate” (3.584 [2.101-5.883]). Females with the “Severe” grade suffered higher odds of depression by 334.0% relative to “Mild”, while males had a relative risk of 258.4%. In conclusion, the present data provide systematic insights into the IMC-induced depression risk and updated the related clinical knowledge. Furthermore, the IMCPR classification approach could be used as an effective tool to evaluate this risk.